The Effect of the Local Government Financial Information Systems and Auditor Competence on Audit Quality - Ririn Akhriani; Haliah Hasan; Nirwana Nirwana (Indonesian Journal of Business Analytics, 2023)
This study aims to determine and analyze the effect of the Local Government Financial Information System and Auditor Competence on Audit Quality. Data collection using questionnaire techniques involved 32 respondents consisting of auditors and PPUPD at the Bantaeng Regency Regional Inspectorate Office. The analysis method used is Multiple Linear Regression Analysis. The results of this study prove that the Local Government Financial Information System and Auditor Competence partially have a positive and significant effect on audit quality. Local Government Financial Information System and Auditor Competence simultaneously affect audit quality by 0.414 or 41.4% . This research can be used as evaluation material for the Internal Government Auditor, especially for the Bantaeng District Inspectorate, in improving the quality of their audits.